A Study on Learning Styles: Visual, Auditory and Kinesthetic at English Literature Students of STIBA Persada Bunda Pekanbaru - Karnedi, Karnedi (RC-INSTITUT, 2017)
This was a case study research that had purposes to describe the students’ learning styles (Visual, Auditory and Kinesthetic) tendency or the most dominant style and analyze quantitatively and qualitatively in the English subjects at the English Literature Students’ of Sekolah Tinggi Ilmu Bahasa Asing Persada Bunda Pekanbaru. The data were collected by giving a quetionnaire that was based on the learning styles indicators. The questionnaire was given on Thursday and Wednesday on the October 11 to 12 2017. There were 120 population and 41 samples. The result of the research showed that among 41 students, 15 of them had Auditory learning style, 10 of them were Kinesthetic and 4 of them were Visual. Meanwhile, the rest of them, 12 were the combination between 2 styles. It meant that they had the same amount of two learning styles.